2018
DOI: 10.1117/1.jbo.23.10.107004
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for rapid assessment of blood lithium levels in ultramicro volumes of blood plasma for applications in personal monitoring of patients with bipolar mood disorder

Abstract: Bipolar disorder (BD) is a common mental health condition, characterized by extreme changes in mood, energy, and behavior. BD is often managed through mood-stabilizing medications, of which lithium formulations remain the most reliable and effective at reducing the risk of suicide. To achieve adequate and consistent efficacy, lithium concentrations need to be maintained within a narrow therapeutic range (0.4 to 1.2 mmol∕L). Because of its narrow therapeutic index, long-term lithium therapy is associated with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…The UV–visible spectrum of PLu in Figure a revealed peaks at 290 and 420 nm. The 290 nm peak was associated with the π–π* transition, while the 420 nm peak was correlated to the n –π* transition as reported in our previous studies. The same peaks appeared at 300 and 405 nm, respectively, in the theoretically computed spectrum. The experimental UV–visible spectrum of OBB/PLu-20/80 (Figure b) revealed peaks at 350 and 430 nm, whereas the theoretical spectrum revealed peaks at 350 and 450 nm.…”
Section: Results and Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The UV–visible spectrum of PLu in Figure a revealed peaks at 290 and 420 nm. The 290 nm peak was associated with the π–π* transition, while the 420 nm peak was correlated to the n –π* transition as reported in our previous studies. The same peaks appeared at 300 and 405 nm, respectively, in the theoretically computed spectrum. The experimental UV–visible spectrum of OBB/PLu-20/80 (Figure b) revealed peaks at 350 and 430 nm, whereas the theoretical spectrum revealed peaks at 350 and 450 nm.…”
Section: Results and Discussionsupporting
confidence: 83%
“…Lithium chloride was chosen as a model compound along with a lithium carbonate drug, which is widely used to treat mental disorders such as bipolar disorder. 24 The drug has a narrow therapeutic index, and long-term effects can increase the chances of toxicity. 24 Hence, a technique is required that can provide rapid measurement of lithium in an accurate manner to improve the compliance of lithium treatment with possible reduction in toxicity.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, while electrical impedance spectroscopy offers exceptional accuracy in detecting conductivity variations, electrical impedance sensing using non-functionalized electrodes lacks specificity to a single element. Therefore, it was demonstrated that the integration of optical and impedance measurements offering a high degree of selectivity and sensitivity, respectively, could provide an improved method for lithium determination [ 56 , 57 , 58 ]. Titrimetric analysis has also been coupled with optical spectroscopy to achieve Li+ detection, utilizing an ionophore-based titration reagent [ 59 ].…”
Section: Advances In Therapeutic Monitoring Of Lithium Levelsmentioning
confidence: 99%